Workplace changes, perceived difficulties and migration intentions among Romanian construction workers during the covid-19 pandemic - Vasile Chasciar; Denisa Ramona Chasciar; Claudiu Coman; Vasile Gherhes; Cristel Iotu; Adrian Netedu (PLoS ONE, 2026)
The COVID-19 pandemic disrupted labour mobility across Europe, but its effects varied substantially across sectors. Construction remained relatively active in Romania, creating a specific context in which workers faced health-related constraints while maintaining employment continuity. This article examines how construction workers in Brașov County perceived workplace changes, pandemic-related difficulties and migration intentions during the COVID-19 pandemic. The study is based on a questionnaire survey conducted among 384 construction workers, with data collected online in February–March 2022. Descriptive statistics were used to summarise workers’ perceptions, working conditions and migration intentions, while chi-square tests of independence and Spearman’s rank-order correlation were applied to examine associations between sociodemographic variables, perceived difficulties, financial impact and willingness to work abroad. The findings indicate that most respondents reported limited changes in workload and working conditions, while the main difficulties were related to mask wearing, compliance with sanitary rules and extended project completion times. Although the overall intention to work abroad was low, perceived financial impact was positively associated with willingness to migrate. The study contributes worker-level evidence on labour mobility intentions in an essential sector during a period of restricted international movement.